EVALUASI PELAKSANAAN RENCANA STRATEGI DINAS PENDAPATAN DAERAH PROVINSI RIAU TAHUN 2009-2013 - Indah Riatama; Zaili Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Department of Revenue strip of Riau Province as one of the regional government which has duties and functions to manage local revenue that is necessary for the provision of financing penyeleggaraan governance, development, the vision of local Revenue Office in Riau Province should constitute part of a strategic and integral in its efforts to realize vision Riau Province which consists of a long-term vision and menengahyang term vision is the crystallization of the commitment of the whole society Riaubaik Province for the construction of long-term and medium-term development has been defined by Regulation strip of Riau Province.In this case I want to see how the policy program of the Strategic Plan Revenue Service Riau Province, the Strategic Plan can also be used as a means to undertake activities implemented within one year for the whole range of the Regional Revenue Office of Riau Province, the Strategic Plan also provide feedback that is needed in decision-making and planning in the future by the leaders of the management and entire staff Riau Provincial Revenue Office so that would be obtained performance improvement towards a better future. To analyze these problems the author uses the theory Dunn, 1994: 405 in Subarsono Ag, 2006: 126 which is consistent with the theory that problem. This research is a descriptive qualitative approach, where data collection technique is a technique of observation and interviews with key informants as key informants.Determination of Strategic Planning at the Department of Revenue Riau Province has been sufficiently supported by the accountability and competence of the employees, the work achieved quite reach the target, execution of the work being done already planned and systematic thus the need for a policy to conduct employee performance improvements so that the achievement of the Strategic Plan determination can be effectively achieved.Keywords: Evaluation, Strategic plan implementation, Riau Provincial Revenue Office